1994
DOI: 10.1111/j.1365-2990.1994.tb01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Spread of malignant lymphoid cells into rat central nervous system with intact and disrupted blood–brain barrier

Abstract: The pathways of spread of malignant lymphoid cells into the central nervous system (CNS) were studied using a T lymphoblastic leukaemia/lymphoma model of inbred PVG rats. The effects of intraperitoneal, intracarotid, intravenous, intrathecal and intracerebral routes of transplantation were analysed, and the significance of the blood-brain barrier (BBB) in preventing neoplastic cell invasion was studied by disrupting the BBB with focal cold injury. Extraneurally transplanted cells appeared first in the dura and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Even though animal lymphoma models with differing CNS dissemination exist, [7][8][9] no model demonstrated ocular infiltration by the lymphoma cells. This stems, in part, from the lack of adequate in vivo experimental models.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Even though animal lymphoma models with differing CNS dissemination exist, [7][8][9] no model demonstrated ocular infiltration by the lymphoma cells. This stems, in part, from the lack of adequate in vivo experimental models.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…However, lymphoma cells hypothetically spread from retroperitoneal lymph nodes or bone marrow to the leptomeninges via the intervertebral nervous plexus (9). Aho et al (4) reported that malignant cells appeared to enter the CNS through a deficiency in the BBB around the subarachnoid vessels. Composite meningioma and lymphoma has been reported as a form of tumor-to-tumor metastasis (10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, computed tomography (CT) and magnetic resonance imaging (MRI) abnormalities surrounding hemorrhagic and postoperative changes make it difficult to distinguish between onset of disease and postoperative complications, including metal artifacts. However, malignant cells that enter the CNS appear first in the dura and subarachnoid space in rats with a blood brain barrier (BBB) disrupted by focal injury following exposure to a cold temperature (4). Previous history of subarachnoid hemorrhage (SAH) and aneurysm clipping may be associated with CNS infiltration in systemic lymphoma.…”
Section: Introductionmentioning
confidence: 99%